The Effectiveness of the Problem-Based Learning Model Assisted by Augmented Reality on Learning Outcomes of Natural and Social Sciences in Solar System Material - Fajriatus Arfani; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2025)
Learning models and media that are less in accordance with Permendikbudristek Number 16 of 2022 concerning Process Standards have an impact on low learning outcomes. This study examines the effectiveness of the Problem-Based Learning (PBL) model assisted by augmented reality (AR) on the learning outcomes of grade V science students at SD Gugus Kenanga, Songgom District, Brebes Regency. This type of research is experimental research with a Quasi Experiment design in the form of Nonequivalent Control Group Design. Data collection techniques were in the form of test techniques (pretest and posttest); non-test techniques, namely observation, interviews, questionnaires, and documentation. Initial data analysis techniques included normality and homogeneity tests and final data analysis with t-tests and N-Gain. The output of the t-test was in the form of sig. of 0.000 (sig. <0.05), so H0 is rejected and Ha is accepted. The N-Gain test output of the experimental class is 0.60 and the control class is 0.32. In conclusion, the AR-assisted PBL model is effective and has a higher average increase compared to the teacher-assisted PBL model with image media on the learning outcomes of class V science science at SD Gugus Kenanga, Songgom District, Brebes Regency.